2022
DOI: 10.1177/87564793221120430
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera Lotion Used as a Potential Alternative Couplant for Sonography, in a Low-Resource Health Care Facility

Abstract: Objective: This study assessed the use of Aloe vera lotion as an alternative coupling medium for ultrasound imaging. Materials and Methods: A prospective analytical research design was adopted. A total of 50 subjects who consented were randomly recruited into the study from the University of Calabar Teaching Hospital (UCTH), Calabar and the Gijuwie Medical Diagnostics, Calabar. A total of 50 image pairs were obtained on scanning with Aloe vera lotion (Image A) and commercial ultrasound gel (Image B) for compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Letter to the Editor Dear Editor, I read with interest the recent article "Aloe vera Lotion Used as a Potential Alternative Couplant for Sonography, in a Low-Resource Health Care Facility" by Paulinus et al 1 The authors describe the use of a homemade aloe vera-based lotion that they found to be suitable for use as an acoustic coupling agent for sonographic imaging. The authors concluded that Aloe vera lotion has suitable acoustic transmission compared with commercial coupling gel.…”
mentioning
confidence: 99%
“…Letter to the Editor Dear Editor, I read with interest the recent article "Aloe vera Lotion Used as a Potential Alternative Couplant for Sonography, in a Low-Resource Health Care Facility" by Paulinus et al 1 The authors describe the use of a homemade aloe vera-based lotion that they found to be suitable for use as an acoustic coupling agent for sonographic imaging. The authors concluded that Aloe vera lotion has suitable acoustic transmission compared with commercial coupling gel.…”
mentioning
confidence: 99%